A Study on the Influence and Mediating Effect of Training Intensity, Psychological Resilience and Cultural Literacy on the Performance Ability of Chinese Standard Dance Players - Wu, Yu; Zhou, Liang (Journal of Ecohumanism, 2024)
This study aims to explore the effects of training intensity, psychological toughness and cultural literacy on the performance ability of Chinese standard dance players, and to analyze the mediating effect of psychological toughness as a mediating variable. By analyzing the quantitative data of a large number of Chinese standard dance players, this study constructed a prediction model of performance ability and revealed how training intensity and cultural literacy affect the overall performance of players through psychological toughness. The study found that both training intensity and cultural literacy significantly affected the performance ability of players, and psychological toughness played an important mediating role in this process. Specifically, moderate training intensity can improve the physical ability and technical performance of players, while a high level of cultural literacy helps to enhance the artistic expression and performance appeal of players. Psychological toughness can not only directly improve the performance ability of players, but also play a bridging role in the influence of training intensity and cultural literacy on performance ability. The results of this study provide a theoretical basis for optimizing the training strategy of Chinese standard dance players, and provide a new perspective for exploring how multiple factors interact to affect sports performance ability in future studies.